Embryonic Amygdalar Transplants in Adult Rats with Motor Cortex Lesions: A Molecular and Electrophysiological Analysis - Jimenez-Diaz, Lydia; Nava-Mesa, Mauricio O.; Heredia, Margarita; Riolobos, Adela; Gomez-Alvarez, Marcelo; Criado, Jose María; de la Fuente, Antonio; Yajeya, Javier; Navarro-Lopez, Juan D. (Frontiers in Neurology, 2011)
Transplants of embryonic nervous tissue ameliorate motor deficits induced by motor cortex lesions in adult animals. Restoration of lost brain functions has been recently shown in grafts of homotopic cortical origin, to be associated with a functional integration of the transplant after development of reciprocal host-graft connections. Nevertheless little is known about physiological properties or gene expression profiles of cortical implants with functional restorative capacity but no cortical origin. In this study, we show molecular and electrophysiological evidence supporting the functional development and integration of heterotopic transplants of embryonic amygdalar tissue placed into pre lesioned motor cortex of adult rats. Grafts were analyzed 3 months post-transplantation. Using reverse transcriptase quantitative polymerase chain reaction (RT-qPCR), we found that key glutamatergic, GABAergic and muscarinic receptors transcripts were expressed at different quantitative levels both in grafted and host tissues, but were all continuously present in the graft. Parallel sharp electrode recordings of grafted neurons in brain slices showed a regular firing pattern of transplanted neurons similar to host amygdalar pyramidal neurons. Synaptic connections from the adjacent host cortex on grafted neurons were electrophysiologically investigated and confirmed our molecular results. Taken together, our findings indicate that grafted neurons from a non-cortical, non-motor-related, but ontogenetical similar source, not only received functionally effective contacts from the adjacent motor cortex, but also developed electrophysiological and gene expression patterns comparable to host pyramidal neurons; suggesting an interesting tool for the field of neural repair and donor tissue in adults.